A STUDY ON THE WORK ENVIRONMENT OF FAZAIA INTER COLLEGES DIFFERENT SECTIONS (PRIMARY, SECONDARY AND COLLEGE) - Azra Jamil; Dr Sidra Rizwan; Ansa Nighat Iqbal (International Journal of Contemporary Issues in Social Sciences, 2024)
The study entitled “A study on the work environment of Fazaia Inter Colleges, different sections” was conducted to explore the difference of work environment of three sections of Fazaia Inter colleges. The study was descriptive in nature having quantitative approach. It was conducted through cross-sectional survey design. The main variable of study was work environment. Work environment had eleven sub-scale. Data was collected by using questionnaire from the sample of study. From the total population of 2143 teachers, sample of 411 teachers was selected by using cluster sampling method. Questionnaire was correctly filled by 338 teachers which was 82 percent of selected sample. For the verification of hypothesis and research questions, the researcher used simple descriptive statistics and one-way ANOVA. The data was analyzed with the help of SPSS 21.Study results indicated that out of eleven sub-scales of work environment significant difference exist among three sections in relation to job satisfaction, communication satisfaction, organizational commitment, co-worker relationship, compensation satisfaction and work load whereas results of overall work environment scale indicated that there was a no significant difference in the work environment of different section (Primary, Secondary and College) of Fazaia Inter Colleges. The researcher concluded that there are many factors other than work environment which may affect teachers’ performance. Recommendations were also made on the basis of study results.